Remagnetization of lava flows spanning the last geomagnetic reversal. Issue 2 (18th May 2017) - Vella, Jérôme; Carlut, Julie; Valet, Jean-Pierre; Goff, Maxime Le; Soler, Vicente; Lopes, Fernando
Summary: Large directional changes of remanent magnetization within lava flows that cooled during geomagnetic reversals have been reported in several studies. A geomagnetic scenario implies extremely rapid geomagnetic changes of several degrees per day, thus difficult to reconcile with the rate of the earth's core liquid motions. So far, no complete rock magnetic model provides a clear explanation. We revisited lava flows sandwiched between an underlying reverse and an overlying normal polarity flow marking the last reversal in three distinct volcanic sequences of the La Palma Island (Canary archipelago, Spain) that are characterized by a gradual evolution of the direction of their remanent magnetization from bottom to top. Cleaning efficiency of thermal demagnetization was not improved by very rapid heating and cooling rates as well as by continuous demagnetization using a Triaxe magnetometer. We did not observe partial self-reversals and minor changes in magnetic grain sizes are not related to the within-flow directional changes. Microscopic observations indicate poor exsolution, which suggests post-cooling thermochemical remagnetization processes. This scenario is strongly reinforced by laboratory experiments that show large resistance to thermal demagnetization when thermoremanence was acquired over a long time period. We speculate that in the present situation exsolution was reactivated during in field reheating and yielded formation of new magnetite, yet magnetic domain state rearrangements could also play a role. Initial reheating when the overlying flow took place, albeit moderate (less than 200–300 °C), was enough to produce overlying components with significantly higher unblocking temperatures.